Representasi Ciuman Romantis-Seksual dalam Film Ada Apa dengan Cinta? - Eva Ulviati (Jurnal ILMU KOMUNIKASI, 2019)
This study aims to identify and analyze representations of romantic-sexual kissing in Indonesian fiction films, those are Ada Apa dengan Cinta? (2001) and Ada Apa dengan Cinta? 2 (2016). This study uses the kissing concept of Linda Williams (2008) which links the presence of kisses to the terminology of romanticism and sexuality and Willem Frijhoff’s (2014) shape and type of kissing that influence the meaning of kisses. The kissing scenes in both films was identified by Roland Barthes’s semiotics method. The results of the study indicate that those two films contain romantic-sexual kissing that further strengthens romantic and sexual ideologies.